Zgoda małżeńska w kanonicznym systemie prawnym a oświadczenie o zawarciu małżeństwa w prawie polskim rodzinnym - Urbanowska-Wójcińska, Dorota (Ius Matrimoniale, 2014)
Matrimonial consent constitutes a marriage-forming element in Polish family law as well as in canon marriage law. A constitutive nature of this consent, i.e. a consent that creates a marital relationship, makes it a legal phenomenon in these two legal systems. Canon martial consent shows a number of common characteristics with a declaration of marriage in Polish family law. Both of these systems have been correlated for ages. Now, however, they operate in parallel in relation to Polish Roman Catholic citizens. The shape of a Polish legal regulation is a esult of a long-time evolution influenced undoubtedly by canon marriage law. The aim of the article is to compare a legal structure of contracting a marriage in Polish family law and in canon marriage law as well as to establish their legal nature.